СТРУКТУРА МАГНІТНОГО ПОЛЯ ТОРЦЕВОГО ДУГОСТАТОРНОГО АСИНХРОННОГО ДВИГУНА З ДИСКОВИМ БІМЕТАЛЕВИМ МАСИВНИМ РОТОРОМ - Ращепкін, А.П.; Карлов, О.М.; Крищук, Р.С. (Інститут електродинаміки Національної академії наук України, 2017)
As the title implies, the article describes the method for calculating of axial arc-stator induction motor with solid three-layer disc rotor. It gives attention to the linear velocity of the rotor, which not uniform across gap, and consideration of the edge effect on the thickness gap between the stators. This article gives a detailed analysis of mathematical model of the magnetic field of the motor. The basis of the equation for magnetic field is the Maxwell's equations. Solution of the magnetic field equation uses integral transforms: Fourier series and integral transformation in finite limits. Solving the equation takes into account the actual current placement of slots in the form of the Dirac delta function on surface of the stator in air-gap. It takes into account the frontal part of the current, primary and higher harmonics magnetic field too. The current is specified as complex amplitudes for each phase of the three-phase single-layer and dual-layer compensated arc-stator windings. Plots showing the 3-dimensional magnetic field distribution in the gap between the stators of the axial arc-stator induction motor. References 8, figures 6, table.